The Permeability of Granite Weathering Soil in Tanjungpinang, Bintan Island, Indonesia - Fery Erawan; Emi Sukiyah; Johanes Hutabarat; Adjat Sudradjat (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
Bintan Island is a part of Riau Islands Province. On this island, the capital city is Tanjungpinang. The compliance of public facilities such as landfill waste is a priority in this city. Landfill design that suitable in this area is a sanitary landfill system. The soil layer uses to cover the waste in this landfill system. The closure did gradually avoid the disruption of waste processing. The type of soil for its landfill cover has to be able to control the leachate. It controlled by the permeability of the soil. The methods used in this study are the analysis of the physical and mechanical properties of soil. Rock and soil samples are obtained systematically through trenching. Sampling-based on changes in physical properties of soil that reflect its mechanical properties. A probabilistic approach used to solve the problems and to get accurate results. The geomorphology of the study area divided into four units. They are very flat terrain, flat terrain, slightly steep hills, and steep hills. The sample used for the study is undisturbed soil. Analysis of the physical and mechanical properties of soil shows the types of soil, such as SW, GM, MH-OH, and CH. However, MH is the most dominant type of soil. Each of the soil types represents a certain degree of weathering. The degree of weathering in the study area varies from the III degree to VI degrees. Rocks are weathering form clay mineral, which compiles the soil. Clay mineral in the soil layer is varied from quartz, illite, kaolinite, gibbsite, goethite, and hematite—the impact of the swelling of clay. The swelling of clay in the study area ranged from low to high. The properties and composition of the soil are affected by the permeability value.